Soil phosphorus functional fractions and tree tissue nutrient concentrations influenced by stand density in subtropical Chinese fir plantation forests - Fang, Xiang-Min (PLoS One, 2017)
Stand density regulation is an important measure of plantation forest management, and phosphorus (P) is often the limiting factor of tree productivity, especially in the subtropics and tropics. However, the stand density influence on ecosystem P cycling is unclear in Chinese fir (Cunninghamia lanceolata) plantations of subtropical China. We collected rhizosphere and bulk soils, leaves and twigs with different ages and roots with different orders to measure P and nitrogen (N) variables in Chinese fir plantations with low density (LDCF) and high density (HDCF) at Fujian and Hunan provinces of subtropical China. Rhizosphere soil labile P, slow P, occluded P and extractable P were higher in LDCF than HDCF at two sites. Meanwhile, P and N concentrations of 1-year-old leaves and twigs were higher in LDCF than HDCF and leaf N/P ratio generally increased with increasing leaf age at two sites. Rhizosphere vs. bulk soil labile P and occluded P were greater in LDCF than HDCF at Fujian. Nitrogen resorption efficiencies (NRE) of leaves and twigs were higher in LDCF than HDCF at Fujian, while their P resorption efficiencies (PRE) were not different between two densities at two sites. The average NRE of leaves (41.7%) and twigs (65.6%) were lower than the corresponding PRE (67.8% and 78.0%, respectively). Our results suggest that reducing stem density in Chinese fir plantations might be helpful to increase soil active P supplies and meet tree nutrient requirements.